2009
DOI: 10.4049/jimmunol.0803560
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Is Up-Regulated in Allergic Airway Inflammation and Regulates IL-12p35 Expression

Abstract: Allergic airway inflammation is characterized by marked in situ changes in gene and protein expression, yet the role of microRNAs (miRNAs), a new family of key mRNA regulatory molecules, in this process has not yet been reported. Using a highly sensitive microarray based approach, we identified 21 miRNAs with differential expression between doxycycline-induced lung-specific IL-13 transgenic mice (with allergic airway inflammation) and control mice. In particular, we observed over-expression of miR-21 and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
463
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(492 citation statements)
references
References 84 publications
21
463
3
5
Order By: Relevance
“…Il-12p35 mRNA can be targeted by miR-21 in macrophages and DCs, leading to restricted adaptive Th1 responses. [99][100][101] miR-106 has been demonstrated to target Il-10 mRNA, 102 while miR-29 suppresses immune responses against intracellular pathogens by targeting IFN-c. 103 Numerous cytokine encoding mRNAs are regulated by RNA-binding proteins (RBPs) through the AU-rich elements in their 39-UTR, which may play a vital role in mRNA stabilization. MiRNAs can also cooperate with these RBPs to regulate mRNA stability or translation.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xymentioning
confidence: 99%
“…Il-12p35 mRNA can be targeted by miR-21 in macrophages and DCs, leading to restricted adaptive Th1 responses. [99][100][101] miR-106 has been demonstrated to target Il-10 mRNA, 102 while miR-29 suppresses immune responses against intracellular pathogens by targeting IFN-c. 103 Numerous cytokine encoding mRNAs are regulated by RNA-binding proteins (RBPs) through the AU-rich elements in their 39-UTR, which may play a vital role in mRNA stabilization. MiRNAs can also cooperate with these RBPs to regulate mRNA stability or translation.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xymentioning
confidence: 99%
“…Some of the differentially expressed 28 miRNAs are known to be involved in inflammatory lung diseases and PAH. For example, miR-126, -21, and -26a are important in asthma (17,18,21); let7d, miR-21, -155, and -29 are important in IPF (26); and miR-146a, -155, -21, -25, and -26a are important in PAH (14). Here, we found that expression of each of these miRNA was significantly changed by sevoflurane anesthesia; therefore, sevoflurane anesthesia may affect lung diseases such as asthma, IPF, and PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutating miR-21 binding sites in IL-12p35 3'-untranslated region abrogated miR-21-mediated repression. Thus, IL-12p35 is likely the direct target of miR-21 (Lu et al, 2009b). These researchers further generated miR-21 deficient mice.…”
Section: Il-12mentioning
confidence: 99%
“…miR-21 was initially identified to inhibit IL-12p35 in a reporter system (Lu et al, 2009b). Furthermore, mutating miR-21 binding sites in IL-12p35 3'-untranslated region abrogated miR-21-mediated repression.…”
Section: Il-12mentioning
confidence: 99%